Internalisasi Nilai Toleransi dalam Pembelajaran Pendidikan Agama Islam di Sekolah: Studi Kasus di SMP Negeri 12 Sidey, Kabupaten Manokwari, Provinsi Papua Barat - Endah Muthoharoh; Siti Nurhaliza Koniyo (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Indonesia is a religiously, ethnically, and culturally plural nation, which makes the cultivation of tolerance from school age a non-negotiable necessity, particularly in regions with interreligious populations such as West Papua. This study aims to describe the process of internalizing tolerance values in Islamic Religious Education (PAI) learning at SMP Negeri 12 Sidey, Manokwari Regency, West Papua Province, and to identify the supporting and inhibiting factors involved. This study employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving the Principal, PAI teachers, general subject teachers, and several students, and were then analyzed using the interactive model of Miles and Huberman, comprising data condensation, data display, and conclusion drawing, with validity established through source triangulation. The results show that PAI teachers carried out the internalization of tolerance values through three stages consistent with Muhaimin's framework (2001): value transformation through verbal delivery and reinforcement with Qur'anic verses, value transaction through discussion and two-way interaction, and value transinternalization through exemplary conduct and daily habituation. Supporting factors include inclusive school policy, the active role of PAI teachers as role models, relevant curriculum content, and cooperation from parents and the school committee. Inhibiting factors include students' still-superficial understanding of tolerance, the diversity of students' socio-economic backgrounds, the scarcity of contextual teaching media reflecting West Papuan local wisdom, and the potential for friction among students stemming from ethnic and religious differences.